Explaining the Role of Faculty members of medical sciences universities in Dealing with Epidemics: A Qualitative Study - Maryam Khoshbakht-Pishkhani; Fariba Asgari; Mehrnoosh Khoshtrash; Nastran Mirfarhadi (Caspian Journal of Health Research, 2023)
Background: The roles of Faculty members of medical sciences universities in responding to and controlling critical situations and epidemic diseases are critical and of great importance. Objective: This study was aimed to explain the role of faculty members in dealing with epidemics and crises. Materials and Methods: This qualitative study was conducted using a content analysis method at Guilan University of Medical Sciences in 2020. Thirteen faculty members (physician, Ph.D. in nursing, anesthesiologist, PhD in reproductive health, and Ph.D. in disaster and emergency health) were selected through purposive sampling method, and their viewpoints were surveyed until data saturation was reached. Data were collected through semi-structured interviews. Qualitative content analysis was used to analyze the data. Results: Based on participants’ experiences, several roles could be considered under 3 main categories: a public educator, a clinical therapist, and a manager. Each of these main categories included several sub-categories.  Based on the participants’ experiences, among faculty members’ roles, the public educator, as the most central role, influences other duties of faculty members. Conclusions: The results of this study showed that medical faculty members have numerous and significant roles in dealing with crises and emerging diseases. Identifying the medical faculty’s roles in coping with epidemics can help better understand the capabilities of these instructors and plan a basis for their greater cooperation and participation in controlling, preventing, and managing crises and emerging diseases. The results of this study can be advantageous in planning training programs and preparing faculty members to deal with epidemics and crises.